Mindfulness-Based Student Training Leads to a Reduction in Physiological Evaluated Stress - Voss, Andreas; Bogdanski, Martin; Langohr, Bernd; Albrecht, Reyk; Sandbothe, Mike (Frontiers in Psychology, 2020)
BACKGROUND AND OBJECTIVE In today’s fast-paced modern lifestyle, chronic stress has become a serious issue with potential consequences for our physical and mental health. The concept of mindfulness and its derived Mindfulness-Based Stress Reduction (MBSR) program is considered to be an effective stress management technique for patients as well as for healthy persons. The effects of MBSR interventions on their participants have been subject of previous research, especially with regard to psychological or social science approaches using self-reports and questionnaires. In contrast, medical investigations in this field have been less frequent and often somehow limited, for example addressing only absolute (discrete) mean values for heart rate or blood pressure. METHOD In this study, we have evaluated a Mindfulness Based Student Training program (MBST) by applying methods of biosignal analysis to examine its impact on the training participants’ autonomic regulation. This intervention program included classical MBSR elements but was adapted to suit the normal daily needs of university students. We obtained the electrocardiogram, finger-pulse plethysmography and respiration activity from students participating in either the intervention group (IGR, 38 subjects) or a passive control group (CON, 35 subjects) prior to and after 8 weeks of MBST intervention. RESULTS When comparing various indices from heart rate variability, pulse wave variability and respiration in linear and nonlinear domains, significant changes in the autonomic regulation were observed for the IGR group after 8 weeks of MBST. CONCLUSION The results indicate a reduced stress level exclusively for the intervention participants, and therefore, we assume a health benefit from the MBST program.